(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Iron nutritional anemia is a nutritional problem in Indonesia, with the prevalence in pregnant women increasing from 37.1 percent (Riskesdas 2013) to 48.9 percent and the highest prevalence is in the ages of 15-24 years, namely 84.6 percent (Riskesdas 2018). Blood supplement tablets with the dosage and type of iron compounds according to the recommendations of the World Health Organization (WHO) is a program of the Indonesian Government to tackle the problem of anemia in pregnant women which has now become a national program for adolescents and women of childbearing age. The first Blood supplement tablets used contained 60 mg of elemental iron from excicated iron sulfate (200 mg) and 250 mcg of sulfuric acid. Due to low acceptability, on November 11, 2014, the Minister of Health Regulation No. 88 of 2014 was issued with a change and choice of compound to 180 mg of iron fumarate and 400 mcg of folic acid. The use of old blood supplement tablets is only permitted for a maximum of 2 years after the issuance of this Minister of Health Regulation. Changes in the type of iron compound, folic acid dosage and also the packaging are expected to increase the acceptability of these iron tablets. Efforts to overcome the iron nutritional anemia problem by increasing the acceptability and health of the target group are continuing. Currently, there is a global discourse to use MMS in the treatment of iron deficiency anemia. This review discusses TTD and MMS from a health perspective.